From Poverty Eradication to Economic Empowerment: The Impact of the Kudumbashree Program on Women Entrepreneurs in Kerala - Gupta, Gaurav; Chalil, Krishnan (Journal of Advanced Research in Humanities and Social Sciences, 2023)
Economic development is greatly impacted by entrepreneurship, which drives job creation, fosters innovation, enhances living standards, fuels growth. Effective entrepreneurship Policy and the inclusion of women in entrepreneurship are crucial to maximising the impact of entrepreneurship on a country’s economy. In this manner, the government launches various programmes to support entrepreneurial environments. In this regard, this study focuses on the role played by the Kudumbashree programme in fostering women’s entrepreneurship in Kerala, India. The study aims to understand the contribution of Kudumbashree micro-enterprises to the development of women-owned businesses. The research uses secondary sources, including Kudumbashree’s website, research findings, data, to analyse the program’s impact on women’s entrepreneurship. The Kudumbashree program, implemented by the Kerala State Poverty Eradication Mission aims to eradicate poverty and empower women. It features a three-tiered structure for its female community network and has earned recognition as the National Resource Organization under the National Rural Livelihoods Mission. The conclusion of the study highlights the significance of empowering women through entrepreneurship for economic development and notes that organisations such as Kudumbashree have the potential to make a crucial impact in supporting female entrepreneurs. How to cite this article: Gupta G. From Poverty Eradication to Economic Empowerment: The Impact of the Kudumbashree Program on Women Entrepreneurs in Kerala. J Adv Res Humani Social Sci 2023; 10(1): 1-7. DOI: https://doi.org/10.24321/2349.2872.202301